FILM TITLES AS A MATERIAL OF THE LINGUISTIC ASPECT (Scientific journal of the Fergana State University, 2023)
The article discusses important aspects of the study of film titles from a linguistic point of view. Filmonyms (film titles) are an important part of cinema and are said to perform the function of naming, informing, identifying, anticipating, attracting attention, motivating the audience. The titles of the film also include literacy, brevity, conciseness, full coverage of the content of the work, naming, imagining the content of the work, captivating, motivating to watch the film, informing, expressing the whole meaning, imagery.